Introduction of the novel and scarce meters in Simin Behbahani poetry - داود محمدی (مطالعات زبانی و بلاغی)
In first encounter with Simin Behbahani poetry the application of novel and unprecedented meters and versatility and plurality of prosodic meters in her poetry are significant. She offers a particular novelty to her poems by innovations in meters of her own poetry and she also made new and untried methods in Persian poem by proceeding modern concepts of the time in figures of novel meters. Up to 90 percent of Simins poems which were composed between 1352 â 1381 have novel and scarce meters. However, at first her poems do not seem to be rhythmic because readers are not familiar with Simins novel meters, but gradually by the more application of the meters and becoming familiar with them, their elegance and beauty will be sensed. Never the less Simin tried further than various traditional and prevalent meters, over 63 novel and unprecedented metes, and 25 rare and scarce meters on whole. In this article we will introduce the novel and invented meter and the scarce and unprecedented meter in Simins poetry and we will represent one sample of her poem for each meter.